A Quantum Pointer Signal Processing Research - Shuyue Wu; Jingfang Wang (Institute of Advanced Engineering and Science, 2016)
In quantum gray-scale image processing, the storage in quantum states is the color information and the position information According to the advantage of small range of the gray scale in a gray-scale image, a novel storage expression of quantum gray-scale image is proposed and demonstrated in this study. Besides, a new concept of